Comparative Analysis of Malaysia's Islamic Bank Aqad with Indonesia - Iksan; Wardah Yuspin (Proceeding International Conference Restructuring and Transforming Law, 2022)
Malaysia and Indonesia are countries in Southeast Asia that have experienced fairly rapid developments related to Islamic banking. But behind the success of Islamic banking, in the implementation and implementation of each country has a different interpretation. The study in this paper tries to perform a comparative analysis of contractsMurabaha, Mudharabah and Musharakain two countries, namely Malaysia and Indonesia. The research method used is normative legal research using a statutory and conceptual approach. The results showed that there were differences in interpretation in the application of the three contracts. In Malaysia AkadMurabaha is applied in three ways, namely:Bai Al Inah, Bay Al Dayn and Bay Bitthaman Ajjilwhile in Indonesiabai' li al-amri bi al-syira'andBai Al-Dayn.Mudharabah in Malaysia uses two namely:Mudharabah Mutlaqahis a contract in which the rabbul mal allows the mudarib to manage the capital of the mudarabah without special restrictions and the mudarabah muqayyadah is a contract in which the rabbul mal imposes special restrictions on the terms of the mudarabah. Meanwhile, in Indonesia, the mudharabah muqayyadah, mudharabah muthlaqah, mudharabah tsuna`iyah and mudharabah musytaraqah contracts are used. The last musharaka contract. In Malaysia using Shirkah al-Milk and Syirkah al-`Aqd while in Indonesia using Syirkah amwal and known as syirkah inan.